Efficiency of central banks during financial crisis: quantitative easing's economic impact analysis in European Union - Divanach, Anais Marie (2019)
In 2015, the European Central Bank, decides to involve in unconventional monetary policies in order to reinforce economic and monetary European situation after the 2008’s global crisis. This dissertation aims to show the positive as well as the negative impacts that the policy of quantitative easing has had on the European economy and finance. Since these policies have only recently been introduced in the European Union, the method chosen to measure their impacts is to use historical facts such as the use of these policies in Japan, to use the various academic theories and finally to use ECB financial and economic data. Additionally , the thesis shows what other tools could have been used or could be used in the context of non-conventional policies, but also what are the possible outcomes of these policies and how this could affect the independence of the European Central Bank.